Targeting post-translational modifications of Foxp3: a new paradigm for regulatory T cell-specific therapy - Riaz, Farooq; Huang, Zhihui; Pan, Fan (Frontiers in Immunology, 2023)
A healthy immune system is pivotal for the hosts to resist external pathogens and maintain homeostasis; however, the immunosuppressive tumor microenvironment (TME) damages the anti-tumor immunity and promotes tumor progression, invasion, and metastasis. Recently, many studies have found that Foxp3+ regulatory T (Treg) cells are the major immunosuppressive cells that facilitate the formation of TME by promoting the development of various tumor-associated cells and suppressing the activity of effector immune cells. Considering the role of Tregs in tumor progression, it is necessary and pivotal to identify several new therapeutic drugs to target and deplete Tregs in tumors. Although several studies have developed strategies for targeted deletion of Treg to reduce the TME and support the accumulation of effector T cells in tumors, Treg-targeted therapy systematically affects the Treg population and may lead to the progression of autoimmune diseases. It has been understood that, nevertheless, in disease conditions, Foxp3 undergoes several definite post-translational modifications (PTMs), including acetylation, glycosylation, phosphorylation, ubiquitylation, and methylation. These PTMs not only elevate or mitigate the transcriptional activity of Foxp3 but also affect the stability and immunosuppressive function of Tregs. Various studies have shown that pharmacological targeting of enzymes involved in PTMs can significantly influence the PTMs of Foxp3; thus, it may prevent the progression of cancers and autoimmune diseases. Overall, this review will help researchers to understand the advances in the immune-suppressive mechanisms of Tregs, the mechanism of Treg accumulation in tumors, the post-translational regulations of Foxp3, and the therapeutic potential of targeting PTMs in Foxp3 stability. Besides reviewing the potential therapeutic targets and strategies to target the Tregs in TME to improve anti-tumor immunity, we highlight the use of combinational therapy in maximizing the anti-tumor immune responses.